A study of clinicopathological features and outcomes of crescentic glomerulonephritis - P., Pavan Kumar; Ganesan, Vasanth; Gurusamy, Venu (International Journal of Research in Medical Sciences, 2020)
Background: Crescentic Glomerulonephritis (CrGN) is characterized by rapidly progressive renal failure. Most of the literatures have defined >50% crescents in biopsy as CrGN. Only very few studies have included the presence of <50% crescents as CrGN. Methods: To assess the clinico-pathological features and outcome of CrGN with >10% crescents on renal biopsy and comparing them splitting our diagnosis into Immune Complex Mediated CrGN (ICCGN) and non-immune complex mediated CrGN (NICCGN) groups. Results: ICCGN was the commonest group. When compared to ICCGN group, NICCGN patients were older, anuric, had more glomerular necrosis and severe IFTA in biopsy at presentation, more became dialysis dependent at index visit discharge. When patients with >50% crescents in both the groups were compared similar results were seen except that infective complications and proliferative lesions were more in ICCGN. When patients with <50% crescents in both the groups were compared similar findings were seen except that no difference was seen in clinical features and dialysis dependency between them. Conclusions: Oliguria at presentation, Hb <9 g/dl, index visit eGFR<15 ml/min, crescents >60%, moderate to severe IFTA are the independent risk factors for dialysis dependency at index visit discharge.